PERANCANGAN KATALOG PROMOSI PRODUK THE HAPPY SHOP - ODARIO TANTRA YUDHA D.Y, Dr. Budiwirman, M.Pd. San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
The Happy Shop is a women's clothing store is devoted to themed casual clothing in the city of Padang, in line with the needs and interests of high society towards women's fashion in the city of Padang. However, The Happy Shop yet have a catalog in the media campaign and as a differentiator from competitors. Interest Design catalog as a complete media campaign regarding products The Happy Shop.The method of analysis used in the design catalog The Happy Shop approach SWOT analysis (Strength, Weakness, Opportunity, Threat). The orientation of the development of design ideas include the identity of the major media and media support in the form of catalog of T-shirts, paper bag, cards, posters, pins, key chains, x-banner, sales invoices, stickers, hang tags. Hopefully, by the design of this catalog can provide a meaningful contribution through positioning, in addition to strengthening the competitiveness of the competitors boutique clothing that has been developed at this time.Keyword : The Happy Shop, Katalog, Promotion, Products